SESQUITERPENE LACTONES FROM TANACETUM-DENSUM SUBSP AMANI - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 1993)
In addition to known eudesmanolide and germacranolide sesquiterpene lactones a new eudesmanolide, 1beta,4alpha,6alpha-trihydroxyeudesm-11-en-8alpha,12-olide was isolated from the aerial parts of Tanacetum densum subsp. amani. The structure of the new compound was established by spectral data; it showed weak antimicrobial activity.
Keywords: TANACETUM-DENSUM SUBSP AMANI; COMPOSITAE; SESQUITERPENE LACTONES; GERMACRAN-OLIDES; EUDESMANOLIDES; 1-BETA,4-ALPHA,6-ALPHA-TRIHYDROXYEUDESM-11-EN-8-ALPHA,12-OLIDE; PARTHENOLIDE; FLAVONOIDS; ANTIBACTERIAL ACTIVITY